Diversification of teacher’s activity for holistic development of children in pre-school education practice - Mikelsone, Ilze; Grava, Jana; Pavitola, Linda (International Dialogues on Education Journal, 2017)
Holistic approaches involve integration of thinking and activities, inclusive ways of working with complex, cross-curricular, interdisciplinary and transcendental connections (Learning for the future, 2011, p. 7). Assessment of existing situations shows that teachers struggle with diversifying learning form and content and with varying the pace of work as well as the difficulty level of tasks. The holistic approach determines that one particular learning or activity sphere cannot exclude the others and that all of them are interconnected in a complex and nuanced way; therefore it is essential to identify the existing links between them. In pre-school education praxis the learning process is still divided into certain subjects with little emphasis on the integrated approach. In the process of implementing the learning content, the curriculum is composed of more than one particular situation or a case. The aim of this article is to describe the positive experience of teachers in terms of diversification of their activities and to determine the diversification principles which can help the pre-school children to discover their uniqueness and enable them to share their subjective experience as well as recognize the link between their lives and the outside world. As the result of this study, the diversification principles of teachers’ activities have been determined for the holistic development of children.